Green production of sugar by membrane technology: How far is it from industrialization? - Hao Zhang; Jianquan Luo; Lulu Liu; Xiangrong Chen; Yinhua Wan (Green Chemical Engineering, 2021)
Application of membrane filtration in sugar production is attractive because it can reduce the usage of chemicals, produce high-quality clarified juice, and obtain various high value-added products. However, some technical problems, such as insufficient membrane performance, high sucrose loss in membrane retentate, severe membrane fouling, and incomplete cleaning protocols, limit its industrial applications. In order to facilitate the development of membrane technology for sugar production, this review summarizes recent progress on the applications of membrane filtration in different stages of sugar production as well as the integrated membrane processes for various purposes. Moreover, some important issues including membrane fouling, membrane cleaning, economic feasibility and engineering problems of the membrane-based sugar production process are discussed. Finally, the existing challenges and future research prospects for the industrialization of this green technique are pointed out.